Recent advances in Fe‐N‐C single‐atom site coupled synergistic catalysts for boosting oxygen reduction reaction - Katam Srinivas; Zhuo Chen; Hesheng Yu; Dawei Liu; Jian Zhen Ou; Ming‐qiang Zhu; Yuanfu Chen (Electron)
Abstract Metal–air batteries, fuel cells, and electrochemical H2O2 production currently attract substantial consideration in the energy sector owing to their efficiency and eco‐consciousness. However, their broader use is hindered by the complex oxygen reduction reaction (ORR) that occurs at cathodes and involves intricate electron transfers. Despite the significant ORR performance of platinum‐based catalysts, their high cost, operational limitations, and susceptibility to methanol poisoning hinder broader implementation. This emphasizes the need for efficient non‐precious metal‐based ORR electrocatalysts. A promising approach involves utilizing single‐atom catalysts (SACs) featuring metal–nitrogen–carbon (M‐N‐C) coordination sites. SACs offer advantages such as optimal utilization of metal atoms, uniform active centers, precisely defined catalytic sites, and robust metal–support interactions. However, the symmetrical electron distribution around the central metal atom of a single‐atom site (M‐N4) often results in suboptimal ORR performance. This challenge can be addressed by carefully tailoring the surrounding environment of the active center. This review specifically focuses on recent advancements in the Fe‐N4 environment within Fe‐N‐C SACs. It highlights the promising strategy of coupling Fe‐N4 sites with metal clusters and/or nanoparticles, which enhances intrinsic activity. By capitalizing on the interplay between Fe‐N4 sites and associated species, overall ORR performance improved. The review combines findings from experimental studies and density functional theory simulations, covering synthesis strategies for Fe‐N‐C coupled synergistic catalysts, characterization techniques, and the influence of associated particles on ORR activity. By offering a comprehensive outlook, the review aims to encourage research into high‐efficiency Fe single‐atom sites coupled synergistic catalysts for real‐world applications in the coming years.